Juridical Implications On The Implementation Of The Position Of A Notary In Processing Business Licenses Online Through OSS RBA (Online Single Submission Risk Based Approach) - Yehezkiel Caestama Sinaga; Mohamad Fajri Mekka Putra (Faculty of Law, Universitas Pekalongan, 2025)
Licensing is a crucial aspect in business to ensure orderly administration, which is a prerequisite for establishing a business entity. Notaries, who have the responsibility to make authentic deeds in the process of establishing an entity, have limited authority based on the Law on the Position of Notaries. Often, notaries are involved in licensing activities using the Online Single Submission Risk-Based Approach (OSS RBA), although this is not specifically regulated in the regulations that apply to notaries. The author raises the issue regarding the limitations of the responsibilities that notaries have in carrying out business permits in the process of obtaining business permits through the RBA OSS and the relevant legal provisions for notaries involved in processing these permits. The research method in this research is doctrinal legal research using a legislation-based approach. The results of the research reveal that regulations related to risk-based licensing do not explicitly give authority to notaries to process business permits only with a power of attorney. Apart from that, sanctions against notaries who violate the provisions in processing business permits through the RBA OSS have not been adequately regulated in the code of ethics or the Law on Notary Positions.